Trends in atmospheric new-particle formation : 16 years of observations in a boreal-forest environment - Nieminen, Tuomo; Asmi, Ari; Dal Maso, Miikka; Aalto, Pasi P.; Keronen, Petri; Petaja, Tuukka; Kulmala, Markku; Kerminen, Veli-Matti (Finnish Environment Institute, 2016)
Peer reviewed